LEGAL AND ETHICAL CHALLENGES OF SURROGATE MATERNITY: LEXICOLOGICAL ASPECT, COMPARATIVE ANALYSIS AND REGULATORY PERSPECTIVES - Bećirović-Alić, Maida; Spalević, Žaklina; Belović, Jelena; Lubura Ćosić, Majida; Mojašević, Tomica (ACADEMIC REVIEW, 2025)
Contemporary society and the transformations of the traditional family have brought with them the appearance of new phenomena that open numerous legal, ethical and social issues, especially regarding non-traditional forms of marriage and motherhood. One of the most complex and controversial forms of biomedically assisted reproduction is surrogate motherhood, i.e. contractual birth of a child for another person or couple. Although it represents hope for many who cannot become parents naturally, this institute is legally prohibited in numerous countries and in certain cases subject to criminal liability - depending on whether it is an altruistic or commercial form of surrogacy. The legislator must especially take into account the fact that this form of birth for many couples represents the only possibility to have a child with whom they would be genetically related, however, commercial surrogate motherhood increases the risk of instrumentalization and creation of a business, which violates the dignity of surrogate mothers for the sake of a certain fee, which aims exclusively at earnings. This paper analyzes the normative challenges of surrogacy, shedding light on the ethical dilemmas that accompany it, as well as the need to establish a clear legal framework - both at the national and international level. Comparative legal analysis points to significant differences in the approach to this phenomenon, while at the same time emphasizing the necessity of unification and harmonization of legal norms in order to prevent abuses and suppress reproductive tourism.